2023
DOI: 10.1109/access.2023.3235922
|View full text |Cite
|
Sign up to set email alerts
|

Unexploitable Games and Unbeatable Strategies

Abstract: Imitation is simple behavior which uses successful actions of others in order to deal with one's own problems. Because success of imitation generally depends on whether profit of an imitating agent coincides with those of other agents or not, game theory is suitable for specifying situations where imitation can be successful. One of the concepts describing successfulness of imitation in repeated two-player symmetric games is unbeatability. For infinitely repeated two-player symmetric games, a necessary and suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2025
2025
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Because it has been known that TFT is unbeatable in two-player symmetric potential games [43], relation between unbeatability and ZD strategies was focused on, and it was indeed shown that unbeatable TFT is a ZD strategy [39]. Furthermore, relation between the existence of unbeatable imitation [44] and that of unbeatable ZD strategies in two-player symmetric games [23] and in multi-player totally symmetric games [40] has also been shown. These application studies show that the concept of ZD strategies can be useful as methods to control multi-agent systems and to analyze human behavior.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because it has been known that TFT is unbeatable in two-player symmetric potential games [43], relation between unbeatability and ZD strategies was focused on, and it was indeed shown that unbeatable TFT is a ZD strategy [39]. Furthermore, relation between the existence of unbeatable imitation [44] and that of unbeatable ZD strategies in two-player symmetric games [23] and in multi-player totally symmetric games [40] has also been shown. These application studies show that the concept of ZD strategies can be useful as methods to control multi-agent systems and to analyze human behavior.…”
Section: Introductionmentioning
confidence: 98%
“…In the field of information and communications technology, ZD strategies have been applied in resource sharing in wireless networks [27,28], smart grid systems [29], mining in blockchain [30,31], crowdsourcing [32,33], mobile crowdsensing [34], the Internet of Things [35], cloud computing [36], federated learning [37], and data trading [38], in order to unilaterally realize some favorable states. Another field of application is analysis of imitation in behavioral science [39,40]. Originally, in the prisoner's dilemma game, it was pointed out that the Tit-for-Tat (TFT) strategy [41,42], which imitates the previous action of the opponent, is a ZD strategy which unilaterally equalizes the payoffs of two players [1].…”
Section: Introductionmentioning
confidence: 99%